Additive manufacturing in biomedical applications - Narayan, Roger (ASM Handbook ;, 2022)
"Volume 23A provides a comprehensive review of established and emerging 3D printing and bioprinting approaches for biomedical applications, and expansive coverage of various feedstock materials for 3D printing. The volume includes articles on 3D printing and bioprinting of surgical models, surgical implants, and other medical devices. The introductory section considers developments and trends in additively manufactured medical devices and material aspects of additively manufactured medical devices. The polymer section considers vat polymerization and powder-bed fusion of polymers. The ceramics section contains articles on binder jet additive manufacturing and selective laser sintering of ceramics for medical applications. The metals section includes articles on additive manufacturing of stainless steel, titanium alloy, and cobalt-chromium alloy biomedical devices. The bioprinting section considers laser-induced forward transfer, piezoelectric jetting, microvalve jetting, plotting, pneumatic extrusion, and electrospinning of biomaterials. Finally, the applications section includes articles on additive manufacturing of personalized surgical instruments, orthotics, dentures, crowns and bridges, implantable energy harvesting devices, and pharmaceuticals."--